Self-medication in Chinese residents and the related factors of whether or not they would take suggestions from medical staff as an important consideration during self-medication - Ge, Pu; Li, Qiyu; Dong, Murong; Niu, Yuyao; Han, Xiao; Xiong, Ping; Bao, Yuhan; Min, Hewei; Liu, Diyue; Wang, Suqi; Zhang, Jinzi; Zhang, Ziwei; et al. (Frontiers in Public Health, 2022)
Objective To investigate the status of Chinese residents' self-medication behavior and the important factors to consider when purchasing OTC drugs, and to explore the related factors of the possibility that Chinese residents take medical staff's suggestions as important factors to consider when purchasing OTC drugs. Study design A cross-sectional survey. Methods A questionnaire was developed for exploring the sociodemographic characteristics of the respondents, their self-medication status, and important considerations. The questionnaire includes several scales including Health Literacy Scale-Short Form (HLS-SF), EQ-5D Visual Analog Scale (EQ-5D-VAS), Big Five Inventary-10 Items (BFI-10), and New General Self Efficacy Scale (NGSES). After carrying out a multi-stage sampling method, the questionnaire was conducted nationwide from July 10 to September 15, 2021. Next, descriptive statistics were conducted to analyze the general features. Logistic regression was then used to analyze the related factors of the possibility that the respondents took the suggestions of medical staff as an important consideration when purchasing OTC drugs. Results Nine thousand two hundred fifty-six qualified questionnaires were received. 99.06% of Chinese adults had self-medication behaviors. The types of OTC drugs purchased most by the respondents were NSAIDs (5,421/9,256 people, 58.57%) and vitamins/minerals (4,851/9,256 people, 52.41%). 86.2% of the respondents took the suggestions of medical staff as an important consideration when purchasing OTC drugs. The results of multi-factor logistic regression showed that women, those living in the central and western regions of China, those suffering from chronic diseases, those with high agreeableness, high conscientiousness, high neuroticism and openness, high health literacy, high EQ-5D-VAS, and those with high self-efficacy are more likely to take medical staff's suggestions as important factors to consider. Conclusion The vast majority of Chinese adults have self-medication behavior. Important considerations when purchasing OTC drugs include medical staff's suggestions, drug safety and drug efficacy. Whether residents take the suggestions of medical staff as an important consideration is related to their sociological characteristics, agreeableness, conscientiousness, neuroticism, openness, health literacy, self-assessment health status, and self-efficacy. When purchasing and using OTC drugs, residents should carefully listen to the suggestions from medical staff. They should also carefully consider their own conditions before buying OTC drugs.